Penyuluhan dan Pelatihan Mengenai Kesehatan Gigi dan Mulut Kepada Siswa/i SDN Tanjung Duren Selatan 01 Pagi - Talenta Theresia, Tiarma; Roro Asyurati Asia, Raden; Lestari, Sri; Erri Astoeti, Tri (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
Oral health needs to be considered from an early age. The behavior of maintaining dental and oral health is supported by knowledge. Dental and oral health education is one of the efforts made to increase elementary school age children's knowledge and behavior about dental and oral health. The aim of this program is to determine the knowledge of students in grades 4 and 6 at SDN Tanjung Duren Selatan 01 Pagi after dental and oral health education. This study used a descriptive observational method with a cross sectional design. The sampling technique is purposive sampling. The sample for describing knowledge was 139 students in grades 4 and 6 of SDN Tanjung Duren Selatan 01 Pagi. The knowledge of grade 4 and 6 students at SDN Tanjung Duren Selatan 01 Morning before dental and oral health education was in the poor category. After the education was carried out, the understanding and knowledge of grade 4 and 6 students at SDN Tanjung Duren Selatan 01 Pagi increased. Student knowledge regarding the frequency of brushing their teeth, the use of toothpaste containing fluoride and the consumption of cariogenic foods has increased after the dental and oral health education.